(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Anxiety disorders are one of the most common mental health concerns worldwide, affecting millions of people (0). Because traditional therapies at times fail to produce complete relief, complementary and alternative methods are now being sought with increasing interest. The current research focuses on Ayurveda, a traditional Indian medicine system, and its use in treating anxiety issues. Therefore, in this review, through the study of literature and analysed clinical data, we have tried to enlighten the Ayurveda perspective on generalised anxiety disorder (GAD) by highlighting essential herbal medicines as well as therapeutic strategies. The finding of this paper provides some unique information to support the efficacy of certain lived-in care medicines (especially in Ashwagandha, Brahmi), says a study. Nevertheless, the existence of methodologic constraints in current studies confirms our belief that this question still should be explored more thoroughly. This article contributes to the ever-growing research in the field of integrative mental health and provides a background for further investigation into Ayurvedic interventions targeting anxiety.